A Study on the Construction of Emotion Recognition Based on Multimodal Information Fusion in English Learning Cooperative and Competitive Mode - Tu, Haihua (Frontiers in Psychology, 2021)
With the development of science and education, English learning has become more and more important. In the past, English learning was mainly based on missionaries, and students were not very motivated to learn. A team learning model based on game is proposed. This paper constructs a cooperative and competitive model of English learning based on multi-modal information fusion. The main manifestation is that students form groups in small groups, and there is a competitive relationship between the groups. The competition among students in learning is the common interest of the entire group, so that the overall interests of each student will be more competitive. This article refers to the main body association model in the literature to adjust English grammar, vocabulary and language perception ability: learn together in team communication to improve students' multifaceted abilities. Finally, a questionnaire was designed. The results show that after changing the English team learning mode and optimizing the English team learning support system of the students’ English learning team, the English learning cooperation and competition model based on multi-mode information fusion proposed in this paper can improve the learning effect by 55%-60% . In all English teaching, the two dimensions of professional knowledge and English ability training are not mutually orthogonal and mutually exclusive, but mutually supportive and interdependent. To form an effective teaching model of "student-centered and teacher-led", active and rich communication and feedback in the classroom is the key, and it also helps to form a gradual teaching and learning cycle.